2(X-1)=3 X+4 POR FAVOR
Soluções para a tarefa
Respondido por
2
2(X-1)= 3x + 4
2x - 2 = 3x + 4
2x - 3x = 4 + 2
- x = 6---->×(-1)
x= - 6
2x - 2 = 3x + 4
2x - 3x = 4 + 2
- x = 6---->×(-1)
x= - 6
Respondido por
0
2.(x-1)=3x+4
2x-2=3x+4
2x-3x=4+2
-x=6
x=6/-1
x=-6
s={-6}
espero ter ajudado!
boa tarde!
2x-2=3x+4
2x-3x=4+2
-x=6
x=6/-1
x=-6
s={-6}
espero ter ajudado!
boa tarde!
Perguntas interessantes
Matemática,
10 meses atrás
Português,
10 meses atrás
Ed. Física,
10 meses atrás
Química,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás
Artes,
1 ano atrás